Prospective study to evaluate the risk factors associated with mortality in neonatal septicemia - Khurana, Mandeep Singh; Malik, Supriya; Narang, Gursharan Singh; Saini, Ritish (International Journal of Contemporary Pediatrics, 2017)
Background: Neonatal sepsis is a clinical syndrome of bacteremia characterized by systemic signs and symptoms of infection in the first month of life. Neonatal sepsis refers to infection occuring within the neonatal period i.e. first 28 days of life for a term baby and up to 4 weeks beyond the expected date of delivery in a preterm baby. Neonatal sepsis is one of the major cause of neonatal morbidity and mortality. Methods: The present study is a prospective observational study conducted in the neonatal intensive care unit (NICU) of Sri Guru Ram Das Institute of Medical Sciences and Research (SGRDIMSAR), Sri Amritsar over a period of one year from January 2015 to January 2016. Aim of the study is to know the incidence of neonatal sepsis, to study bacteriology of neonatal septicemia and to evaluate the risk factors associated with mortality in neonatal sepsis in our hospital. Results: During the study period (January 2015 to January 2016), 727 neonates were admitted in NICU of SGRDIMSAR, Sri Amritsar. Out of them, 109 neonates were diagnosed as having septicemia. Incidence of neonatal sepsis in our hospital in this study is 149.9/1000 neonatal admissions. 59 (54.1%) neonates had positive blood culture. Out of 109 septic neonates, 50 died and 59 survived. Mortality observed in the present study is 45.9%. Conclusions: It is concluded from present study that the main factors associated with neonatal mortality are low birth weight, prematurity, positive blood culture, neutropenia and prolonged prothrombin time. Some of the risk factors like low birth weight and prematurity are preventable by proper antenatal check ups and measures can be taken for safe and hygienic delivery. Babies with risk factors should be monitored closely for early detection of sepsis and the neonates with sepsis having abnormal laboratory parameters should be subjected to appropriate therapeutic intervention in order to decrease the mortality.